2012
DOI: 10.1186/1471-2229-12-169
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis mutant sk156 reveals complex regulation of SPL15 in a miR156-controlled gene network

Abstract: BackgroundThe Arabidopsis microRNA156 (miR156) regulates 11 members of the SQUAMOSA PROMOTER BINDING PROTEIN LIKE (SPL) family by base pairing to complementary target mRNAs. Each SPL gene further regulates a set of other genes; thus, miR156 controls numerous genes through a complex gene regulation network. Increased axillary branching occurs in transgenic Arabidopsis overexpressing miR156b, similar to that observed in loss-of-function max3 and max4 mutants with lesions in carotenoid cleavage dioxygenases. Arab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 59 publications
1
58
0
Order By: Relevance
“…7A), which represent three subgroups of miRNA-regulated SPL genes (Guo et al, 2008). These genes were also chosen because they contribute to the regulation of sepal trichome number in Arabidopsis (Shikata et al, 2009;Yu et al, 2010;Wei et al, 2012). We found that ChSPL3 expression increased stepwise from vegetative to early inflorescence to anthesis stages of development, while ChSPL9 expression increased from early inflorescence to anthesis stages (Fig.…”
Section: Petal Number Regulation By Endogenous Signalsmentioning
confidence: 90%
“…7A), which represent three subgroups of miRNA-regulated SPL genes (Guo et al, 2008). These genes were also chosen because they contribute to the regulation of sepal trichome number in Arabidopsis (Shikata et al, 2009;Yu et al, 2010;Wei et al, 2012). We found that ChSPL3 expression increased stepwise from vegetative to early inflorescence to anthesis stages of development, while ChSPL9 expression increased from early inflorescence to anthesis stages (Fig.…”
Section: Petal Number Regulation By Endogenous Signalsmentioning
confidence: 90%
“…In addition, miR156 overexpression enhances shoot branching in Arabidopsis (Schwarz et al, 2008;Wei et al, 2012) and Brachypodium distachyon . Whether this regulation is related to sugar signaling is, however, unknown.…”
Section: Shoot Branchingmentioning
confidence: 99%
“…Similarly, the transcript level of miR156 is reduced by feedback when the activation-tagged Arabidopsis sk156 mutant overexpresses a miR156-insensitive SPL15 transgene (Wei et al, 2012). In the latter plant, analysis of the miR156 promoter region revealed SPL binding sites with three repeated GTAC core sequences between -200 bp to -220 bp, suggesting that SPL15 is directly (rather than indirectly) controlling miR156 expression (Wei et al, 2012).…”
Section: Mir156-spl Regulatory Networkmentioning
confidence: 96%
“…SPL proteins are characterized by the presence of conserved DNA binding domains that allow them to bind and regulate downstream genes containing a consensus SPL Binding Domain (SBD) element in their promoters (Yamaguchi et al, 2009;Wei et al, 2012). So far, miR156 has been shown to target 11 out of the 17 SPL member genes in Arabidopsis, 11 members of the 19 SPLs in rice, three in tomato and alfalfa, and two in L. japonicus and maize (Mica et al, 2006;Xie et al, 2006;Moxon et al, 2008;Nonogaki, 2010;Wang et al, 2014a;Aung et al, 2015).…”
Section: Mir156-spl Regulatory Networkmentioning
confidence: 99%
See 1 more Smart Citation